PENGARUH INTERNAL CASH FLOW, INTENSITAS MODAL, INSIDER OWNERSHIP, DAN UKURAN PERUSAHAAN TERHADAP CAPITAL EXPENDITURE PADA INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2009-2011 - SILVANA, SILVIA (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
This research was conducted to examine the influence of internal cash flow, capital intensity, insider ownership, and company size on manufacture industry’s capita expenditure that listed on indonesian Stock Exchange period 2009-2011. The population used as many as 144 manufacture’s company listed on Indonesian Stock Exchange period 2009-2011, and used 35 companies as research sampel. Sampling method used in the research is purposive sampling. Pooled data regression was used to examine the model fit and hypothesis test. The test result showed that the best approach is the fixed effect model fit with four independent variables it is found that were able to explain dependent variable about 68.2%. With a 5% significance level, internal cash flow, capital intensity, and insider ownership have significant effect on capital expenditure. While the firm size variable had no significant effect on capital expenditure.